2016
DOI: 10.1080/00224545.2016.1192096
|View full text |Cite
|
Sign up to set email alerts
|

The role of leadership perception as a mediator between managers’ self-monitoring and subordinate attitudes

Abstract: Although the role of social cognition in leadership perception has been emphasized frequently in recent years, research using this approach in an organizational context is rare. This study investigated subordinates' perceptions of their managers as leaders (that is, to what extent they perceive their manager as a leader) as a potential mediating factor explaining the relationship between managers' self-monitoring and their subordinates' attitudes toward their organizations. The study was carried out with middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Recently, Lord et al (2020) highlighted the role of self-categorisation and ILTs-based self-perceptions for leadership self-efficacy (LSE) and MTL and urged for more empirical research examining self-perceptions and individual-level outcomes. Whereas previous research adopted a follower-centric view and showed that followers' self-perceptions of leadership influenced their judgement of actual leaders (Van Quaquebeke et al , 2011, 2014; Türetgen et al , 2017), we will opt for a leader-centric view and argue that leadership self-perceptions against ILTs are fundamental components of the early roots of leadership development.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…Recently, Lord et al (2020) highlighted the role of self-categorisation and ILTs-based self-perceptions for leadership self-efficacy (LSE) and MTL and urged for more empirical research examining self-perceptions and individual-level outcomes. Whereas previous research adopted a follower-centric view and showed that followers' self-perceptions of leadership influenced their judgement of actual leaders (Van Quaquebeke et al , 2011, 2014; Türetgen et al , 2017), we will opt for a leader-centric view and argue that leadership self-perceptions against ILTs are fundamental components of the early roots of leadership development.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…Leaders in the organization should pay more attention to employee development. Leaders need to monitor themselves and adopt a suitable leadership style which prioritizes employees and exhibits supervisory coaching that would contribute to employees improving their job performance (Turetgen, Unsal, & Dural, 2017).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Özalp et al [29] examined a range of subordinates' perceptions of individuals in managerial positions as leaders (i.e., to the extent they may or may not perceive their managers as a leaders) as a potential mediating factor to explain the relationship between managers' self-monitoring and their subordinates' attitudes toward their organizations among middlelevel managers and their subordinates taken from different business organizations in Turkey. They observed that subordinates 'leadership perceptions of their managers mediated the relationship between managers' self-monitoring and their subordinates' affective and normative organizational commitments implying that the managerial "toolbox" is required to present both variance and adaptability to context.…”
Section: Discussionmentioning
confidence: 99%